Efektivitas Full Day School dalam Penanaman Akhlak Siswa di Sekolah Dasar - Arif Susanto; Ari Susandi; Nur Mashani Mustafidah; Sri Yanti (STKIP Singkawang, 2024)
This research was made because it saw the phenomenon today of the rampant student crime, especially in big cities. the erosion of morals in the millennial generation is caused by juvenile delinquency, which disturbs people's lives, both on a small and large scale. This research is qualitative in nature. Using a qualitative descriptive method that produces descriptive data about the Effectiveness of Full Day School in Instilling Student Morals at SD Muhammadiyah 2 Bojonegoro with the method of discussing induction and deduction, and collecting data through observation, interviews and documentation. Data were analyzed qualitatively by means of data collection, data reduction, data presentation, and drawing conclusions. From the results of the study, through the full day school system learning activities begin at 07.00 to 15.30 so that students are fully within the scope of the school and of course monitored directly by the teacher. In an effort to maximize the inculcation of student morals, the school has four strategies which include 1. Uswah method or exemplary 2. Habituation method 3. Advice method 4. Punishment method, which is implemented in religious activities in which students are required to perform the obligatory prayers in congregation , and also Duha prayers in congregation, after the Duha prayers students will be given spiritual cleansing by class teachers and teachers who are competent in their fields. Especially on Fridays, every Friday the first week to foster the social spirit of students, schools implement blessed Fridays where the activity is in the form of sharing packaged food brought by teachers and students.